Clear cell chondrosarcoma of the larynx. (4th September 2018) - Hendriks, Thomas; Cardemil, Felipe; Sader, Chady
Abstract : Chondrosarcomas represent a group of malignant tumours composed of cells producing cartilage, and clear cell chondrosarcomas (CCC) represent a variant of these. A rare case of a laryngeal CCC is presented. The patient was a 70-year-old man who presented with a 6-week history of throat pain, worsening dysphonia and a lump in the neck. Examination revealed a level 3 neck mass and positron emission tomography imaging revealed a metabolically active right laryngeal mass. Biopsies revealed a cartilaginous neoplasm. The patient underwent total laryngectomy, and the pathology confirmed CCC of the larynx. Chondrosarcomas are the most common type of sarcoma in the larynx but the CCC variant is rare. CCC are usually low-grade tumours affecting long bones, with a male predominance. Less than six cases have been described in the literature affecting the larynx. Management of these malignancies is complete surgical excision given the high risk of local recurrence.